(untitled) (Scientific journal of the Fergana State University, 2024)
This article is devoted to the distribution of vegetation cover in the Surkhandarya region based on the laws of altitudinal zones, in which the issues of plant distribution depending on the topography, climate, soil cover and groundwater level along altitudinal zones are studied.